(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Iodine deficiency can lead to a decrease in myocardial contractility, increased peripheral vascular resistance, and lipid metabolism disorders. To determine iodine deficiency as a risk factor for cardiovascular diseases, 42 patients (mean age 65 ± 13 years, 16 males) were studied. Patients were divided into 5 subgroups based on the presence of hypertension, heart failure, cardiomyopathy, coronary dysfunction, and arrhythmia. Urinary iodine concentration (5.29 ± 4.52 mcg/dl) was determined using the Sandell-Kolthoff colorimetric reaction. The greatest decrease in urinary iodine concentration was observed in subgroups with arrhythmia and heart failure (4.7 ± 4.94 mcg/dl and 4.9 ± 4.81 mcg/dl, respectively). In 3 patients, an elevated level of thyroid-stimulating hormone was detected (5.3 ± 1.4 mME/l). In subgroups without arrhythmia, an increase in lipid (cholesterol, triglycerides) levels was noted. Thus, iodine deficiency is common in cardiovascular diseases. Iodine supplements may prevent the worsening of cardiovascular system status under conditions of iodine deficiency.